KADAR SAPONIN DAUN TANAMAN YANG BERPOTENSI MENEKAN GAS METANA SECARA IN-VITRO - Sri Susanti; Eko Marhaeniyanto (Universitas Tribhuwana Tunggadewi, 2014)
The research aims to identify and select of tree foliages as a feed source of protein, saponins and in lower CH4 production in vitro. The research material are 10 tree foliages Hibiscus rosa-sinensis, Linn, Eritrina lithosperma, Gliricidia sepium, Jacq, Calliandra calothyrsus, Meissn, Moringa oleifera, Lamm, Leucaena leucocephala, Swieteria mahagoni, Artrocarpus heterophyllus, Paraserianthes falcataria and Samanea saman. Evaluation of saponin extract from the tree foliages is done by adding a saponin extract on feed control. Control diet consisted of concentrate and forage Zea mays with the proportion of 1:1 crude protein content of 13.3%. The design used a randomized block (RBD) with treatment: R0 = 0.5 g control diet, S1 = R0 + 0.5% saponin extract and S2 = R0 + 1% saponin extract from DM. The variables measured were (a) chemical composition (b) total gas production, (c) the production of CH4, and (d) digestibility DM and OM (DMD and OMD) in vitro. The addition of saponin extract from tree foliages in the control diet caused a decrease in feed digestibility. The use of 1% saponin extract from Hibiscus rosa-sinensis, Linn, Moringa oleifera, Lamm, and Paraserianthes falcataria leaves, lowered DMD and OMD control diet by 7%. Three species Calliandra calothyrsus, Meissn, Moringa oleifera, and Samanea saman shows CH4 production is less than 1%, so the potential to be used as feed ingredients protein source. The highest content of saponins found in Paraserianthes falcataria leaves (15.04%). Use of saponin 1% of Hibiscus rosa-sinensis, Linn, Moringa oleifera and Paraserianthes falcataria leaves lowered the value DMD, OMD control diet for 4,3-6,0% after 96 hours of incubation